Impact of Preparative pH on the Morphology and Photocatalytic Activity of BiVO4 - Yongbiao Wan; Sihong Wang; Wenhao Luo; Lianhua Zhao (International Journal of Photoenergy)
Adjusting pH with an ammonia solution during the synthesis, single-crystalline BiVO4 has been prepared using Bi(NO3)3·5H2O and NH4VO3 as starting materials through aqueous-phase precipitation at room temperature. The prepared samples are characterized by X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), and scanning electron microscope (SEM). The impact of pH on structure, surface morphology, visible-light photocatalytic activity, and light absorption performance of BiVO4 is explored and discussed. During the synthesis process, neither extremely acidic (low pH) nor basic (high pH) conditions are desirable for the formation of BiVO4 in monoclinic phase. The highest photocatalytic performance on the degradation of a methylene blue solution is observed under pH=7.0 for BiVO4 in monoclinic scheelite, which is attributed to its small grain size and marked surface oxygen evolution ability.